2002
DOI: 10.1016/s0960-9822(02)01276-9
|View full text |Cite
|
Sign up to set email alerts
|

Converging Populations of F-Actin Promote Breakage of Associated Microtubules to Spatially Regulate Microtubule Turnover in Migrating Cells

Abstract: We propose that f-actin movement into the convergence zone plays a major role in spatially modulating MT turnover during cell migration by regulating MT breakage, and thus minus-end dynamics, in central cell regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 37 publications
10
90
0
Order By: Relevance
“…In addition, we performed a kymographic analysis of mCherry-actin transfected LLC-PK1 cells. Figure 3C shows a kymograph from the cell shown in Figure 3B (and Supplemental Movie 3B) with an actin retrograde flow velocity of 6.9 Ϯ 0.6 nm/s (n ϭ 4 cells) to be on the time scales of seconds which compares well with the values reported by Gupton et al (2002). To further test the role of actomyosin contractility, we inhibited myosin II ATPase activity with blebbistatin.…”
Section: Actomyosin Contractilitysupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, we performed a kymographic analysis of mCherry-actin transfected LLC-PK1 cells. Figure 3C shows a kymograph from the cell shown in Figure 3B (and Supplemental Movie 3B) with an actin retrograde flow velocity of 6.9 Ϯ 0.6 nm/s (n ϭ 4 cells) to be on the time scales of seconds which compares well with the values reported by Gupton et al (2002). To further test the role of actomyosin contractility, we inhibited myosin II ATPase activity with blebbistatin.…”
Section: Actomyosin Contractilitysupporting
confidence: 79%
“…Because actomyosin contractility has been reported to buckle and break MTs (Waterman-Storer and Salmon, 1997;Gupton et al, 2002;Brangwynne et al, 2006), we directly imaged actin dynamics to determine its contribution to MT bending in LLC-PK1 cells. As shown in Figure 3A (and Supplemental Movies 3A1 and 3A2), we found that F-actin is nearly stationary, whereas MTs are simultaneously observed to deform.…”
Section: Actomyosin Contractilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Our assay of total cellular microtubule polymer is not sensitive enough to detect such differences. In addition, Rac1 activation also increases microtubule turnover and minus end depolymerization caused by increased retrograde flow and microtubule breakage, effectively lowering the total amount of microtubule polymer (7,49). This might also explain why the amount of microtubule polymer in the presence of excess Op18 was only slightly increased in Rac1(Q61L)-expressing cells as compared with control cells.…”
Section: Pak-dependent Phosphorylation Downstream Of Rac1 Canmentioning
confidence: 99%